Web monitoring of industrial signals using embedded systems - Romero-Molano, Cesar Augusto (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2017)
The paper presents the design of software and hardware for a system of web monitoring of industrial signals. This prototype provides a web interface which can observe in real time the status of four industrial-type signal on-off. MSP432 microcontroller is used for sampling and transmitting monitored signals to a Raspberry PI which receives by a UART link the MSP432 monitored data and presents them immediately in the front-end web application. The prototype design was verified with a pneumatic application that consists of four single-acting cylinders and it was observed an efficient synchronization between the occurrence of the triggering event or change in status of any of the monitored cylinder and web publishing.